Gastroprotección en pacientes con polifarmacia: ¿justificada? - Vallejos Narváez, Álvaro; Maldonado Cañón, Laura; Torres Rodríguez, Sandra; Hernandez Díaz, William; Diaz Silva, Dieric; Yate Támara, Camilo (Revista Médica de Risaralda, 2015)
Gastroprotección